(untitled) (Indian Journal of Animal Production and Management, 2013)
The present study was conducted to evaluate the production performance of improved variety Gramapriya birds maintained under AICRP on Poultry breeding at Ranchi Veterinary College, Birsa Agricultural Univerisity, Ranchi (JharKhand). The evaluation of body weight, feed intake, feed conversion ratio, age at sexual maturity, egg production rate and internal egg quality trait such as shell thickness, albumin index and shape index was done. Gramapriya birds had significantly highter body weight, higher feed intake, better FCR, better egg production rate, early sexual maturity and higher egg mass than Desi birds. The study concluded that Gramapriya birds perform better than desi birds of Jharkhand under same management and rearing conditions.